Solve for y 23y-4(5+6y)=-13

Math
23y-4(5+6y)=-13
Simplify 23y-4(5+6y).
Tap for more steps…
Simplify each term.
Tap for more steps…
Apply the distributive property.
23y-4⋅5-4(6y)=-13
Multiply -4 by 5.
23y-20-4(6y)=-13
Multiply 6 by -4.
23y-20-24y=-13
23y-20-24y=-13
Subtract 24y from 23y.
-y-20=-13
-y-20=-13
Move all terms not containing y to the right side of the equation.
Tap for more steps…
Add 20 to both sides of the equation.
-y=-13+20
Add -13 and 20.
-y=7
-y=7
Multiply each term in -y=7 by -1
Tap for more steps…
Multiply each term in -y=7 by -1.
(-y)⋅-1=7⋅-1
Multiply (-y)⋅-1.
Tap for more steps…
Multiply -1 by -1.
1y=7⋅-1
Multiply y by 1.
y=7⋅-1
y=7⋅-1
Multiply 7 by -1.
y=-7
y=-7
Solve for y 23y-4(5+6y)=-13

Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top